Damage modes of the aeronautic multidirectional carbon/epoxy composite T300/914 in machining. (30th June 2008) - Iliescu, Daniel; Gehin, Daniel; Nouari, Mohammed; Girot, Franck
Damage mechanisms of tipped tungsten carbide tools have been investigated when dry machining of multi-directional carbon fibre composites. The objective of this study is to determine the effects of the cutting parameters on the tool?workpiece interface and to identify the different wear modes. Different rake angles (0?, 15? and 30?), and feed rates (0.05, 0.1 and 0.2 mm/rev) were tested for a constant cutting speed (60 m/min). The cutting loads were determined, and the tool surface topography was analysed using complementary techniques. All aspects of material removal were found to be primarily dependent on the fibre orientation.